Evaluasi Penerapan Eco-Label dalam Pengembangan Ekowisata di Desa Wisata Nglanggeran, Yogyakarta - Husniyah, Jihan Fitri; Dewanti, Sefila Nesya; Cahyani, Siti Nur (Pusat Studi Pariwisata Universitas Gadjah Mada, 2024)
This research was conducted to analyze the application of eco-labels in the development of ecotourism in the Nglanggeran Tourism Village, due to urgency of eco-labels as an official identity that shows the commitment of an ecotourism destination to certain standards related to aspects of nature conservation, local economic empowerment and cultural preservation local to maximize the quality of sustainable ecotourism management. This research uses a qualitative method based on an in-depth literature review to analyze the implementation of eco-labels in the Nglanggeran Tourism Village. The research results show that ecotourism management in the Nglanggeran Tourism Village has fulfilled most of the ideal criteria for an ecotourism destination, even though it has not received eco-label legitimacy from the relevant official institutions. Therefore, it is necessary to have an official eco-label institution to provide an official label as an ecotourism destination in the Nglanggeran Tourism Village so that it can maximize its management, especially in minimizing negative impacts on the environment.